FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KANKER PAYUDARA DI POLIKLINIK ONKOLOGI RSUD ARIFIN ACHMAD PROVINSI RIAU - LPPM Al-Insyirah (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2016)
Breast cancer is the leading cause of death in women worldwide. Based on medical record data Arifin Achmad Hospital Riau province, in 2014 an increase in breast cancer cases that became 584 cases.This study aims to determine the factors associated with the incidence of breast cancer at the Oncology Clinic Arifin Achmad Riau Province in 2015. This type of research is an observational analytic study with case control design (case-control). Case that a part of patients diagnosed with breast cancer and controls that not a part of patients who are diagnosed with breast cancer. The results showed that age (p = 0.002; OR = 2.83), family history (p = 0.009; OR = 2.55), age of menarche (p = 0.028; OR = 2.12), and the use of hormonal contraceptives in a long time (p = 0.008; OR = 2.65) was associated with the incidence of breast cancer. First child-bearing age (p = 0.664; OR = 1.33) and obesity (p = 0.279; OR = 0.47) did not have a significant association with the incidence of breast cancer.